ASPECTS CONCERNING FEM MODELLING OF AN ULTRASONIC HORN USED AT MICRO-EDM DRILLING (Nonconventional Technologies Review, 2016)
The paper deals with finite element modelling (FEM) of complex shape ultrasonic (US) horn that has its end a wire tool-electrode used for micro-drilling by ultrasonically aided electrical discharge machining (EDM+US). The US horn is the technological component of an ultrasonic chain actuated by a sandwich PZT transducer supplied from 40 kHz generator. The shape and dimensions of ultrasonic horn was determined through several stages of FEM modelling strategy, aiming at obtaining the resonance condition of ultrasonic chain, i.e. the equality between natural frequencies of the sandwich PZT transducer and the US horn with included tool. The influence of different constructive conditions of US horn on its natural frequency and amplification were established in order to replicate the modelling strategy for other horn complex form. Finally, the measurements related to resonance conditions validated the strategy of FEM modelling creating conditions of CAM application for horn achievement.
Keywords: finite element modelling; ultrasonic; EDM